NURSES' PERCEPTIONS ABOUT THE OPERATIONALIZATION OF THE NURSING PROCESS IN AN EMERGENCY ROOM. - Matzembacher, Elisama Pricila; Meschial, William Campo; Adamy, Edlamar Kátia; Arboit, Jaqueline; Argenta, Carla; de Oliveira Vargas Bitencourt, Julia Valeria (Revista de Pesquisa: Cuidado é Fundamental)
Objective: to describe nurses' perceptions about the implementation and implementation of the Nursing Process in an emergency room. Method: a descriptive study with a qualitative approach, developed with 10 nurses from a philanthropic hospital in the West of Santa Catarina. Data collection was carried out in July 2021, through a semi-structured interview. Data from the interviews were audio-recorded and later fully transcribed and submitted to Bardin's content analysis. Results: after the analysis, three thematic categories emerged: "Factors that hinder the implementation and implementation of the Nursing Process in the emergency room"; "Opportunities for qualification of assistance with the Implementation and implementation of the Nursing Process" and "Implementation and implementation of the Nursing Process in the emergency room: how we would like it to be". Conclusion: the development of strategic actions to overcome the existing difficulties for the implantation and implementation of the Nursing Process in urgent and emergency services is emerging.